Comparative study of special and ordinary braced frames. (31st January 2012) - Akbas, Bulent; Sutchiewcharn, Narathip; Cai, Wenyu; Wen, Rou; Shen, Jay
SUMMARY The collapse probability of ductile and non‐ductile concentrically braced frames was investigated using nonlinear dynamic response analysis. Two buildings with three and nine stories located in Boston and Los Angeles, respectively, were designed and subjected to ground motions from the areas. In Boston area, three‐story and nine‐story buildings were designed as ordinary concentrically braced frame with response modification reduction factor R equal to 3 1/4 to be considered as non‐ductile structural systems; comparatively, in Los Angeles area, three‐story and nine‐story buildings were designed as special concentrically braced frame with response modification reduction factor R equal to 6 to be considered as ductile structural systems. In order to evaluate the performance of ductile and non‐ductile concentrically braced frames in moderate and severe seismic regions, ATC‐63 would be used as reference to assess the seismic behaviors. Evaluation approach recommended by ATC‐63 was adopted, and hundreds of nonlinear dynamic analyses were performed. Through alternating the scale factors of designated ground motions, median of structural collapse intensity was presented for each structure. By observing the results of statistical performance assessment, the seismic performance of the systems was evaluated, and some observations are made based on the study. Copyright © 2012 John Wiley & Sons, Ltd.